THE SCALE INSECTS OF IRAN (HEMIPTERA: COCCOMORPHA) PART 3 THE SOFT SCALES (COCCIDAE) AND OTHER FAMILIES - Moghaddam, Masumeh; Watson, Gillian W. (Zootaxa, 2024)
The present work is the third and final part in a series of monographs on the Iranian scale insect fauna (Hemiptera: Coccomorpha) by the same authors: Part 1, the armoured scales (Diaspididae), was published in 2021, and Part 2, the mealybugs (Pseudococcidae and Rhizoecidae) and Putoidae, was published in 2022. Here we cover ten families: Asterolecaniidae, Cerococcidae, Coccidae, Cryptococcidae, Eriococcidae, Kermesidae, Margarodidae, Monophlebidae, Ortheziidae and Phoenicococcidae, bringing the total number of scale insect families recorded in Iran to 14. A key is provided to separate all 14 families. For each of the ten families in the present work, keys to identify the genera and species found in Iran are provided. These are accompanied by detailed descriptions, illustrations, distribution data, information on natural enemies, economic importance and the host-plants recorded in Iran. The main purpose of this work is to provide agricultural staff concerned with pest control and quarantine inspection in Iran (and elsewhere) with a reliable means of species identification. Among the recorded species in the present work, Ceroplastes elytropappi (Brain, 1920) and Mesolecanium nigrofasciatum (Pergande, 1898) (Coccidae) are considered to be doubtful records for Iran. Pulvinaria aligarhensis Avasthi & Shafee, 1985 and Pulvinaria urbicola Cockerell, 1893 are both recorded from Iran for the first time.